Pengaruh Perbedaan Komposisi dan Ukuran Partikel Batang Singkong dan Batubara Terhadap Kualitas Bahan Bakar Briket Biocoal - Samudro, Panji Ario; Asmara, Sandi; Kuncoro, Sapto (Jurnal Agricultural Biosystem Engineering, 2023)
A severe energy crisis the Indonesians whose notes had once been members of OPEC or petroleum exporters are particularly tricky.  Coal production Indonesia in 2017 totaled 461 million tons were given priority to the mouth of mine.  With production at a figure of millions of tons of coal, it could be an alternative fuel choice that replaced oil that began to shrink production.  Coupled with a natural adhesive use of the cassava sewage system, it can serve as an alternative energy source called a biocoal briquette. The aim of the study is to see how the composition and the size of the cassava steam and coal particles in the quality of a biocoal briquette.  The research uses complete randomizwd design (CRD) arranged vectorally by three replications.  The first factor is material composition (b) (50%BB:50%BS, 40%BB:60%BS, and 30%BB:70%BS).  The second factor is the scuttle (m) (10mesh, 20mesh, and 30mesh).  Research shows that sewage from the cassava stem is worthy of being used for the manufacture of a biocoal briquette fuel. Producing the following characteristics : water content ranges between5.26-6.77% already meeting the quality standards (SNI 4931/2010) by 17%, the density of the population between 0.37-0.41g/cm³, the rate of arson between 0.35-0.38gr/minute, the kalor rate of between 4.548-5.064cal/g that already meets the kalor class A value standard of 5000-6000 cal/g and class B 4000-5000cal/g. Keywords: Biocoal Briquette, Coal, Cassava.